(3GdEjVGM aj TQM GdeaUds - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3YHO GdMdje Hf eMeO s)
(3ChdgG (B:s
(3CMeO ai JbOje GdeaYhd dJYXjeg GdSGHbjf hGdeJYdjf Ci GdChdjf hGdBNQjf hCaVd UdhGJ GdeUdjf Ci CaVd OYGA GdOGYjf s
(3BNQgG (B:s
(3hEPG aYdhG Pdc ajg adGf jaYdhG ai GdPi de jcf ajg VQH ef VQhH GdJNaja hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs